Impact of Authentic Leadership traits in Engineering Sector using MCDM - Junaid, Muhammad; Sajid, Muhammad (International Conference on Applied Engineering and Natural Sciences, 2023)
This study aims to develop a conceptual model that establishes a connection between Authentic Leadership (AL), employee engagement, and organizational innovation within Pakistan’s engineering sector. Employing a Multi-Criteria Decision-Making (MCDM) technique, the study investigates the interaction and impact of workers on organizational innovation, generating benefits for both industry practitioners and the academic community. The findings highlight the substantial influence of four key AL traits, namely balanced processing, internalized moral perspective, relational transparency, and self-awareness, on work engagement [8]. By applying the Analytic Hierarchy Process (AHP) and utilizing decision-making software, the study identifies the self-awareness as the most crucial criterion for AL outcomes, with a weight of 0.25891. Relational transparency Balanced processing (weight: 0.20894), Balanced processing (weight: 0.1220), and internalized moral perspective (weight: 0.0483) follow as subsequent priorities. These outcomes contribute to the development of theoretical understanding in the field. Furthermore, they provide valuable insights to the engineering sector, enabling the cultivation of employee engagement and the enhancement of organizational innovation. The research focuses on elucidating the relationships between AL, employee engagement, and organizational innovation in the context of Pakistan’s engineering sector. By adopting a comprehensive MCDM approach, the study offers a thorough analysis of the factors influencing employee engagement, with particular emphasis on the identified AL traits. The findings underscore the significance of balanced processing, internalized moral perspective, relational transparency, and self-awareness as drivers of work engagement [9]. Moreover, the application of the AHP technique reveals the priority weights assigned to these traits, highlighting the critical role of the internalized moral perspective criterion in achieving AL outcomes. The results of this research carry implications for both practitioners and scholars. For the engineering sector in Pakistan, embracing and implementing AL practices can yield substantial benefits, fostering a work environment that stimulates employee engagement and drives organizational innovation. By prioritizing the identified AL traits, organizations can effectively channel their resources and efforts towards enhancing employee engagement and promoting innovation. From an academic standpoint, this study contributes to the existing literature by providing empirical evidence and a conceptual model that sheds light on the interplay between AL, employee engagement, and organizational innovation. The findings serve as a foundation for further theoretical development and future research endeavors in this domain.